2014
DOI: 10.3928/23258160-20141118-11
|View full text |Cite
|
Sign up to set email alerts
|

Tele-ophthalmology Screening for Proliferative Diabetic Retinopathy in Urban Primary Care Offices: An Economic Analysis

Abstract: A substantial burden of diabetic retinopathy was identified, most of which was undiagnosed. In a closed system, tele-ophthalmology screening for PDR is likely to be cost-saving across the range of scenarios explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Rachapelle et al 23 showed systematic screening for rural patients with diabetes once every 2 years was cost-effective ($1061–$3183/QALY) compared with no screening, opportunistic or annual screening; however, cost-effectiveness will be dependent on administrative costs of establishing and maintaining regular screening. Brady et al 24 estimated cost savings of $36/patient ($38 telescreening vs $74 no screening), and sensitivity analyses showed that increased prevalence of DR in the target patient population increased cost savings. Richardson et al 25 estimated cost savings of $153.53/patient (~$71 000 over 7 years) from avoiding an additional visit to the ophthalmologist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rachapelle et al 23 showed systematic screening for rural patients with diabetes once every 2 years was cost-effective ($1061–$3183/QALY) compared with no screening, opportunistic or annual screening; however, cost-effectiveness will be dependent on administrative costs of establishing and maintaining regular screening. Brady et al 24 estimated cost savings of $36/patient ($38 telescreening vs $74 no screening), and sensitivity analyses showed that increased prevalence of DR in the target patient population increased cost savings. Richardson et al 25 estimated cost savings of $153.53/patient (~$71 000 over 7 years) from avoiding an additional visit to the ophthalmologist.…”
Section: Resultsmentioning
confidence: 99%
“…Teleophthalmology also reduces the number of patients that require direct referral for examination avoiding unnecessary visits 24. This is most beneficial in rural locations due to reduction of travel cost from remote and geographically isolated areas 29 30.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the results showed that all socioeconomic costs of the medication-based diabetic retinopathy screening model were significantly lower than the physician-based model cost of $173 per person. In general, in many parts of the world, there is a strong logic for telemedicine implementation based on economic, social and cultural aspects [55][56][57]. Another study showed that remote doctor ophthalmologist examination of diabetes retinopathy was very cost effective compared to direct screening by specialists [58].…”
Section: Telemedicinementioning
confidence: 99%
“…The economic impact of eye care telemedicine in a mountainous, rural health center in West Virginia over a period of seven years from 2003-2009 was evaluated in [5]. In [6] established if proliferative diabetic retinopathy (PDR) screening of tele-ophthalmology could be price-saving. In [7], it was proposed that primary care hospitals may use telemedicine to monitor for diabetic retinopathy and track for disease intensifying over a prolonged period of time.…”
Section: Introductionmentioning
confidence: 99%